Dominican Republic - Public Expenditure Review : Reforming Institutions for a More Efficient Public Expenditure Management - World Bank (Washington, DC, 2013)
The economic performance of the Dominican Republic over the past three years, has been less impressive than in the 1990s. During 2001-2002, economic growth slowed down to 3.5 percent per annum on average, due to the combination of external factors (the global economic slowdown and high oil prices), and domestic policy weaknesses. The government responded to the growth slowdown with increased public spending, which led to high deficits, largely financed by foreign borrowing. In 2003, economic performance worsened further, due to a massive banking crisis, epitomized by the collapse of the third largest commercial bank, Baninter, amidst mismanagement, fraudulent banking practices and inadequate banking supervision. With the banking crisis, the electricity crisis and the deterioration in market sentiment, real GDP growth fell to negative 1.3 percent in 2003. Fiscal adjustment, with a view to stabilizing the public debt, is central to the authorities' macroeconomic program supported by an International Monetary Fund - IMF Stand-By Arrangement. The main messages of this Report can be summarized as follows: 1) the Dominican Republic will need to decisively improve the allocation and efficiency of its public expenditures in order to resume economic growth and poverty reduction; 2) there is room for selective expenditure increases in the social sectors, provided the inefficiencies that affect public expenditure in these sectors can be eliminated; 3) steps should also be taken to de-concentrate, and professionalize decisions affecting budget preparation, execution and control, introduce aspects that would better help inform policymakers, and support better policy choices, and improve the monitoring of public spending; and, 4) efforts should be made to professionalize the civil service, and accelerate the decentralization process, sequencing and putting in place the conditions that guarantee sound public expenditure management at the local, as well as central levels of Government.